PENGEMBANGAN ENTREPRENEURSHIP GERABAH KECAMATAN MALO KABUPATEN BOJONEGORO - Dados Susilowati; Retno Muslinawati (ITB AAS INDONESIA Surakarta, 2021)
This study discusses the Development of Pottery Entrepreneurship, Malo District, Bojonegoro Regency. The problem in this research is how is the marketing strategy used in developing the pottery craft business so that it can survive in the midst of intense competition in other handicraft businesses that exist today. The type of research used is qualitative research in the form of applied research, which takes place in the center of the pottery industry, Rendeng Village, Malo District, Bojonegoro Regency. The analysis in this study was carried out using inductive analysis techniques using interactive analysis models and the preparation of community empowerment strategies with SWOT analysis using cross strategies, namely the strategy of utilizing all strengths to seize opportunities, strategies for overcoming weaknesses to seize opportunities, strategies for utilizing all strengths to overcome threats and strategies to overcome weaknesses and threats. Based on the results of the SWOT analysis, eight strategies were produced for the pottery industry in Rendeng Village, Malo District, Bojonegoro Regency, (1) Opening new outlets, (2) Utilizing social media to sell products, (3) Activating promotions, (4) Adding capital to increase sales. production capacity, (5) Improving the quality of products and services, (6) Developing new products, (7) Improving managerial capabilities, (8) Improving the quality of human resources. Keywords: Pottery, Marketing strategy, SWOT analysis